Stylistic Analysis of Margaret Atwood’s The Handmaid’s Tale and Bina Shah’s Before She Sleeps: A Comparative Study of Feminist Dystopian Fiction - Ashraf, Amna; Rabbani, Munazzah (Annals of Human and Social Sciences, 2025)
Feminist Dystopian Fiction has assumed great significance in recent years. In this context, this study probes the impact of culture(s) and linguistic choices in the creation of dystopian narratives written by women. The research explores how the portrayal of feminist issues by contemporary female writers, Margaret Atwood, in The Handmaid’s Tale (1985), and Bina Shah, in Before She Sleeps (2018), is influenced by the cultural settings and stylistic choices. For this purpose, data has been collected through purposeful selection of important sections of text(s) from these narratives and analysed using qualitative textual analysis and Mills’ Feminist Stylistics (1995) framework. The study investigates how gender discrimination, reproductive control, loss of agency and identity are stylistically embedded in Feminist Dystopias. The study concludes that the culture(s) of both authors, namely, a white woman and a woman of color, impact their portrayal of gender discrimination, patriarchy, and loss of agency in their works. Future researchers can also integrate reader-response stylistics.